Organizational Role Stress of Women Agricultural Officers in Kerala - Anshida Beevi C. N. , Monika Wason , R.N.Padaria , Premlata Singh and Eldho Varghese, (Indian Journal of Extension Education, 2017)
Stress can be defined as an adverse reaction that people experience when external demands exceed their internalcapabilities. Empirical studies in recent times focused on the causal factors of stress, stress manifestations, moderators ofstress and strain relationship, types of stress experienced by diverse groups and the types of coping strategies. The presentstudy was conducted in the state of Kerala to study the organizational role stress among women extension personnel.Research design followed in this study was Expost -facto. Asample comprising of sixty women agricultural officers fromKerala State Department of Agriculture were selected through multistage random sampling. Organizational Role Stress(ORS) was measured using a Likert-type scale developed by Udai Pareek (1983) consisting of 50 items divided into 10dimensions. The study found that family role stress is high for women agricultural officers than work role stress. Furthernon-parametric Friedman test showed that there was a statistically significant difference among agricultural officersregarding different role stresses.